2005
DOI: 10.1111/j.1468-2982.2005.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Eletriptan in the Early Treatment of Acute Migraine: Influence of Pain Intensity and Time of Dosing

Abstract: This double-blind, placebo-controlled study was designed to evaluate the efficacy and tolerability of early treatment of a single migraine attack, when headache pain was mild, with two doses (20 mg and 40 mg) of eletriptan. Patients (N = 613; female 79%; mean age 39 years) meeting International Headache Society criteria for migraine were encouraged, but not required, to utilize early treatment, thus providing an opportunity to assess the relative contribution to efficacy of pain severity and timing of dose. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 12 publications
3
99
2
2
Order By: Relevance
“…Pain-free efficacy of migraine pharmacotherapy appears to be enhanced, and the incidence of adverse events appears to be reduced by the practice of early intervention [Goadsby et al 2008;Silberstein et al 2008;Mathew et al 2007;Carpay et al 2004;Brandes et al 2005;Loder et al 2005;Mathew et al 2004;Scholpp et al 2004;Cady et al 2000]. These caveats notwithstanding, the results demonstrate the better performance of sumatriptan/naproxen sodium to sumatriptan monotherapy, naproxen sodium monotherapy and placebo with respect to the rigorous clinical endpoint of sustained pain-free/no adverse events and reinforce the usefulness of utilizing this new composite endpoint.…”
Section: Discussionmentioning
confidence: 70%
“…Pain-free efficacy of migraine pharmacotherapy appears to be enhanced, and the incidence of adverse events appears to be reduced by the practice of early intervention [Goadsby et al 2008;Silberstein et al 2008;Mathew et al 2007;Carpay et al 2004;Brandes et al 2005;Loder et al 2005;Mathew et al 2004;Scholpp et al 2004;Cady et al 2000]. These caveats notwithstanding, the results demonstrate the better performance of sumatriptan/naproxen sodium to sumatriptan monotherapy, naproxen sodium monotherapy and placebo with respect to the rigorous clinical endpoint of sustained pain-free/no adverse events and reinforce the usefulness of utilizing this new composite endpoint.…”
Section: Discussionmentioning
confidence: 70%
“…Correspondingly, in clinical use, triptan efficacy is diminished when allodynia is present during a migraine attack [70]. Several prospective trials have demonstrated substantial improvement of efficacy outcomes when the patient was instructed to treat at a mild level of migraine pain intensity [71][72][73][74][75]. Presumably, mild pain implies that treatment took place prior to the development of cutaneous allodynia, but this cannot be certain.…”
Section: Implications Of the Neuropathic Pain Model For Migraine Treamentioning
confidence: 96%
“…Aufgrund von Posthoc-Auswertungen kontrollierter Studien, open-label-Studien und neuerer kontrollierter Studien mit gezielt früher Einnahme der Testmedikation bei noch milder Schmerzintensität ergibt sich heute die Empfehlung, Triptane bereits bei einsetzendem Kopfschmerz, also zu einem frü-hen Zeitpunkt der Attacke, zu verabreichen [9][10][11]. Hierdurch ergeben sich Vorteile hinsichtlich der Schnelligkeit und des Ausmaßes der Schmerzreduktion [12][13][14]. Die Progression der Attacke bis hin zum Schmerz mit starker Intensität kann so in vielen Fällen verhindert werden.…”
Section: Wann Sollten Triptane Eingenommen Werden?unclassified